Association of Family History of Cardiovascular Diseases in Boys Aged 12-13 Years with Structural and Functional Indicators of the Left Ventricle and Arterial Stiffness in the Age of 43-46 Years (Results of 32-Year Prospective Follow-up) - O. Yu. Isaykina; V. B. Rozanov; A. A. Aleksandrov; I. V. Leontyeva; M. B. Kotova; E. I. Ivanova (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the association of Family History (FH) of cardiovascular diseases (CVD) in boys aged 12-13 years with the development of structural and functional changes in the left ventricle and stiffness of the main arteries in adulthood (43-46 years old) according to prospective study.Material and methods. For the initial examination, boys were selected whose parents suffered from CVD at a young age or died prematurely from them (risk group). The comparison group was formed from a population sample of boys of a similar age without FH of CVD. The examination included a survey on a standard questionnaire, measurement of anthropometric indicators, blood pressure (BP), pulse counting, determination of the blood lipid spectrum. The intima-media complex thickness (IMT) of the common carotid arteries was measured; echocardiography and applanation tonometry were performed.Results. The group with FH of CVD significantly (p<0.05) differed in childhood in terms of the body mass index (BMI) (18.8 vs 17.6 kg/m2), systolic BP (SBP) (117 vs 107 mm Hg), diastolic BP (DBP) (67 vs 56 mm Hg), average BP (81.8 vs 72.7 mm Hg) and triglycerides (0.79 vs 0.58 mmol/L). In adulthood, increased total cholesterol (TC) level (6.3 vs 5.8 mmol/L; p=0.036) and other indicators of atherogenesis were revealed in the risk group. The risk of fatal outcomes from CVD in the next 10 years in men with a family history of CVD in childhood was significantly higher compared to the control group (1.94 vs. 1.28; p <0.001). The main contribution to the total risk of fatal CVD in middle-aged men was made by TC and smoking. In the group with FH of CVD, higher stiffness of the arteries in adulthood was observed. There were found significant (p=0.002) intergroup differences in the IMT (0.73 vs 0.63 mm). A statistically significant positive relationship between BMI and some structural and functional indicators of the left ventricle and stiffness indicators of the main arteries was revealed. DBP and mean BP in childhood are associated with arterial stiffness in adulthood according to the parameters of central SBP and central DBP. BMI in boys is the most significant predictor for most structural and functional indicators of LV myocardial hypertrophy, in particular, LV myocardial mass (private R2=0.140) and interventricular septum thickness (R2=0.164; p=0.001), and arterial stiffness by central DBP parameter (R2=0.043; p=0.024) in adulthood. The risk of increased IMT development in males in adulthood with FH of CVD is 6.1 times higher than that of their peers without FH.Conclusion. FH of CVD revealed in childhood in males is a risk factor for the development of early atherosclerosis and, due to its ease of detection, can be used as one of the criteria for the formation of high-risk groups for the purpose of primary prevention.